Spekulasi (Gharar) dalam Perspektif Hadis Tematik: Analisis Konsep, Larangan, dan Relevansinya dalam Transaksi Kontemporer - Ahmad Ridha Jafar; Muhammadiyah Amin; Abdul Rahman Sakka (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2026)
This study examines the concept of gharar (speculation/excessive uncertainty) through a thematic hadith (ḥadīth mawḍūʽī) approach, focusing on its conceptual definition, the grounds of its prohibition, and its relevance to contemporary transactions. The central problem is the persistent gap between the normative prohibition of gharar established in the Prophetic traditions and the empirical reality of modern transaction models e-commerce, conventional insurance, financial derivatives, cryptocurrency, and digital financing that increasingly embed elements of uncertainty. This research aims to reconstruct the meaning of gharar from authentic hadiths and to formulate operational criteria for distinguishing prohibited (fāḥish) from tolerated (yasīr) uncertainty in present-day muamalah. The study employs a qualitative library research design using the thematic hadith method, complemented by content analysis of the matn and a maqāṣid al-sharīʽah reading. The findings show that the prohibition of bayʽ al-gharar in Ṣaḥīḥ Muslim and the sunan collections is grounded in the protection of property, justice, and consent, rather than in the rejection of risk per se. Accordingly, gharar is graded: excessive uncertainty that dominates a contract and exploits one party is forbidden, whereas minor and unavoidable uncertainty is tolerated. Applied to contemporary practice, the criteria of clarity of object, price, quantity, and time of delivery provide a robust instrument for screening digital and financial transactions for Sharia compliance. The study concludes that thematic hadith analysis remains a living source of normative guidance capable of addressing emerging transaction technologies.